Exploring Students’ Perception on the Benefits of TikTok Content for English Language Learning - Maya Agustina, Riska; Yanuarius Yanu Dharmawan (PT. ALHAFI BERKAH INDONESIA, 2024)
Since its emergence, TikTok has expanded as a social media platform by facilitating the spread of educational content, particularly English language learning, which has become increasingly attractive to students in Indonesia. This study explores students' perceptions of TikTok's effectiveness in enhancing English proficiency. By focusing on emotional experiences and practical usage, it fills a gap in the literature and provides a deeper understanding of TikTok’s educational impact. A qualitative approach involving 70 social media-active students was employed. Data were gathered through questionnaires and interviews, assessing social media use and perceived platform effectiveness. Results showed a strong preference for TikTok as a supplementary English learning tool due to its accessibility and engaging content. However, issues like internet connectivity and privacy concerns were noted. In conclusion, TikTok has potential as a resource for language practice and skill improvement, suggesting the need to integrate social media into educational strategies for more interactive learning environments.